A fast-response, fluorescent 'turn-on' chemosensor for selective detection of Cr3+1. Issue 86 (18th September 2015) - Fan, Chunhua; Huang, Ximing; Black, Cory A.; Shen, Xingxing; Qi, Junjie; Yi, Yuanping; Lu, Zhengliang; Nie, Yong; Sun, Guoxin
<x xml:space="preserve">Abstract</x> A highly selective and sensitive chemosensor 3 for Cr3+ detection was designed and synthesized, which showed a fast turn-on fluorescence response under physiological conditions.